Botulinum toxin injection to improve functional independence and to alleviate parenting stress in a child with advanced pantothenate kinase-associated neurodegeneration: A case report and literature review. Issue 20 (May 2018) - Lin, Cho-I; Chen, Kuan-Lin; Kuan, Ta-Shen; Lin, Sheng-Han; Lin, Wei-Pin; Lin, Yu-Ching
Abstract: Rationale: Pantothenate kinase-associated neurodegeneration (PKAN) is a rare autosomal recessive disease. Progressive motor symptoms such as dystonia and spasticity begin in childhood and relentlessly become incapacitating later in life. Treatments including anticholinergics and iron chelation are usually ineffective. Botulinum toxin type A (BoNT-A) is effective for adult patients with dystonia or spasticity. Patient concerns: We reported a 10-year-old female patient with advanced PKAN, manifesting as generalized dystonia and spasticity. Diagnosis: The patient was diagnosed with PKAN by a pediatric neurologist. Interventions: The patient received BoNT-A injection. Outcomes: The effect was obvious at four weeks after the injection, with an improvement of 25% in Barry-Albright Dystonia Scale and 4% in Functional Independence Measure for Children score. Furthermore, there was a 3.8% reduction in Parenting Stress Index Short Form score and 8.3% improvement in Pain and Impact of Disability domain in the score of Cerebral Palsy Quality of Life for Children. Lessons: BoNT-A injection was effective to improve functional independence and to alleviate stress of caregivers in the patient with advanced PKAN.